Analysis on Smart TV Terminal Industry Situation and Key Technology - Xin Shen; Wenyu Pan; Guqiao Zhu (Dianxin kexue)
The current situation of smart TV terminal industry was introduced.With a general introduction on the influence of the audiovisual service itself and its forms that the terminal is getting“smart”，some key technologies on which these new services are based were given.Based on the analysis on the industry situation and key technologies，it is indicated that the trend of smart terminal is irreversible and would finally change the form of audiovisual service industry.